2021
DOI: 10.1007/s10845-021-01785-0
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to determine the main factors affecting creep rates in laser powder bed fusion

Abstract: There is an increasing need for the use of additive manufacturing (AM) to produce improved critical application engineering components. However, the materials manufactured using AM perform well below their traditionally manufactured counterparts, particularly for creep and fatigue. Research has shown that this difference in performance is due to the complex relationships between AM process parameters which affect the material microstructure and consequently the mechanical performance as well. Therefore, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…If the data (X,Y) is non-linear, the above formulation of SVR will not work. To overcome the issue of non-linearity for SVR, the data are mapped to a higher dimension using a kernel function [35].…”
Section: Svrmentioning
confidence: 99%
“…If the data (X,Y) is non-linear, the above formulation of SVR will not work. To overcome the issue of non-linearity for SVR, the data are mapped to a higher dimension using a kernel function [35].…”
Section: Svrmentioning
confidence: 99%
“…Process monitoring [40] Root cause analysis of process failure [41], Process modelling [42] Process fault prediction [43], Process characteristics prediction [44] Self-optimizing process planning [45], Adaptive process control [46] Machine Machine tool monitoring [47] Fault diagnosis [48], Downtime prediction [49] RUL prediction [50], Tool wear prediction [51] Adaptive compensation of errors [52,53],…”
Section: Processmentioning
confidence: 99%
“…Spherical pores come from gas entrapment and irregular pores form as a result of poor inter track/layer fusion or pores resulting from keyhole closure [21]. Porosity has always been a determining factor for creep performance and has recently been shown to be the most influential factor affecting the creep rate, more so than other LPBF process factors such as build orientation and scan strategy [22]. Another interrupted creep study also found that the main crack initiation points were pores [23], more specifically irregular pores [24].…”
Section: Evolution Of Porositymentioning
confidence: 99%